Comportamento de linhagens de soja obtidas de dois cruzamentos, quanto à raça 3 de Heterodera glycines - Silva, José Algaci Lopes da; Sediyama, Tuneo; Teixeira, Rita de Cássia (Revista Ceres, 1999)
Under the U.F.V. Soybean Breeding Program, 59 soybean lines from Doko RC x Coker and Haitwig x Doko RC crosses were studied for resistance to Heterodera glycines, race 3, the soybean cyst nematode. The experiment was arranged in an entirely randomized design with one plant per plot and 5 replicates. Each pot held about 300 g of a l: l soil and sand mixture and each plant was inoculated at transplanting with about 4000 eggs placed into the seedling planting hole. After approximawa 30 days, plants were evaluated for susceptibility or resistance based on female number counts and according a formula by GOLDEN et alii (5). “FT- Cristalina” was used as the susceptible and “Hartwig' as the resistance control. Only UFV 611909 and 612972 were resistant to Heterodera glycines, race 3, among all 59 tested lines; the remaining was highly susceptible.
Keywords: Linhagens de soja; Cruzamentos; Heterodera glycines